2015
DOI: 10.4103/2008-322x.170360
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and repeatability of refractive error measurements by photorefractometry

Abstract: Purpose:To determine the accuracy of photorefraction and autorefraction as compared to cycloautorefraction and to detect the repeatability of photorefraction.Methods:This diagnostic study included the right eyes of 86 children aged 7-12 years. Refractive status was measured using photorefraction (PlusoptiX SO4, GmbH, Nürnberg, Germany) and autorefraction (Topcon RM800, USA) with and without cycloplegia. Photorefraction for each eye was performed three times to assess repeatability.Results:The overall agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…Regarding the cylindrical results, studies agree with the consistency of the cylindrical power between the Plusoptix and cycloretinoscopy. 34 A similar phenomenon was observed here with 0.50 DC higher results in comparison to retinoscopy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding the cylindrical results, studies agree with the consistency of the cylindrical power between the Plusoptix and cycloretinoscopy. 34 A similar phenomenon was observed here with 0.50 DC higher results in comparison to retinoscopy.…”
Section: Discussionsupporting
confidence: 88%
“…One of the studies had modified the referral criteria for hypermetropia (+1.12 D and +2.60 D instead of +2.00 D and +3.50 D) to get a revised sensitivity value (65.38% to 84.62% and from 46.15% to 69.23%). 34 Few studies have reported the underestimation of refractive error and having higher accuracy in myopia than hyperopia in the pediatric population. 34 35 In this study, an overall hyperopic shift in the values was observed in comparison to retinoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During further analysis, the spherical values agreed well with the emmetropia group ( P = 0.33) compared with the hyperopia group ( P < 0.0001). Regarding the cylindrical results, several researchers agreed with the consistency of the cylindrical power between the device and CR 13 , 15 , whereas others did not 16 , 17 . In the present study, the plusoptiX overestimated the the cylindrical power in all groups, thus resulting in the partial or total underestimation of SE (all P < 0.0001).…”
Section: Discussionmentioning
confidence: 81%
“…The plusoptiX has been reported by the majority of studies to underestimate children’s refractive error and to have higher accuracy in myopic children than hyperopic children 13 – 15 . In the present study, the plusoptiX A12C led to a considerable shift towards myopic values (0.45 D), particularly in the hyperopia group (1.62 D), because of normal accommodation.…”
Section: Discussionmentioning
confidence: 99%